2014
DOI: 10.1007/s11130-014-0409-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Tart Cherry Juice Supplement on Arterial Stiffness and Inflammation in Healthy Adults: A Randomised Controlled Trial

Abstract: (2014). Effect of a tart cherry juice supplement on arterial stiffness and inflammation in healthy adults: a randomised controlled trial. Plant Foods for Human Nutrition, 69 (2), 122-127. Copyright and re-use policy

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
89
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(95 citation statements)
references
References 33 publications
5
89
0
1
Order By: Relevance
“…Lynn et al (2014) found that consumption of a tart cherry juice concentrate evoked a minor increase (p = 0.012) in plasma ferric reducing ability in a group of 25 healthy adults. However, the effect was mostly due to a decreased antioxidant status in the control group.…”
Section: In Vivo Studiesmentioning
confidence: 89%
See 4 more Smart Citations
“…Lynn et al (2014) found that consumption of a tart cherry juice concentrate evoked a minor increase (p = 0.012) in plasma ferric reducing ability in a group of 25 healthy adults. However, the effect was mostly due to a decreased antioxidant status in the control group.…”
Section: In Vivo Studiesmentioning
confidence: 89%
“…This is particularly so in adipose tissue; animals prone to obesity, insulin resistance and hyperlipidemia; and older adults with compromised resistance to oxidative stress. However, the sample sizes studied are very small and the authors did not provide evidence of sufficient statistical power to detect a true difference between placebo and treatment groups [10][11][12][13][14].…”
Section: In Vivo Studiesmentioning
confidence: 97%
See 3 more Smart Citations